PERANAN NOTARIS SELAKU PEJABAT PEMBUAT AKTA TANAH DALAM PROSES VERIFIKASI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KABUPATEN BANYUASIN - Yudi Hardiawan (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
The results of this study indicate that the Sale and Purchase Agreements made before a Notary as Officer of Land deed is authentic deeds, but to be considered authentic deed, deed of sale before it is signed must be preceded by verification BPHTB for verification BPHTB is a requirement that has been determined by the Act that the Sale and Purchase Agreements will be signed after BPHTB paid and verified. The role of the Notary as Officer of Land deed in the manufacture of a deed of sale must ask the parties truth of BPHTB  tax payments BPHTB, if the parties can not submit proof of payment BPHTB the Notary as Officer of the Land Deed authorizes to order and help the parties to pay for and verify BPTHB in DPPKAD to be able to implement sales and purchase agreement something. Supposedly verification conducted by Revenue Service of the regional asset and finace management (DPPKAD) is about truth and completeness of SSPD BPHTB and supporting documents but not the price of the transaction. Then the result of the verification hindrance in BPHTB SSPD becomes obstacles in the issuence of the deed Purchase sale.